Improved high-molecular polypropylene calcium salt as well as preparation process and application thereof
Through the improved preparation process, the yield and quality of polymer polypropylene calcium salt is improved, and multiple stimulus response characteristics and additional functional characteristics are imparted, solving the problems of unstable yield and quality, limited functionality and poor environmental friendliness in traditional methods.
Patent Information
- Application Number
- CN202510221568.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The synthesis method of traditional polymer polypropylene calcium salts has problems such as unstable yield and quality, limited functionality and poor environmental friendliness.
The improved preparation process is adopted, including the preparation of magnesium sulfate solution, monomer mixture preparation, microwave-assisted polymerization reaction, cleaning and purification, intelligent calcification reaction, functional modification and drying treatment. The quality and functionality of the product are improved by introducing functional monomers, intelligent catalysts, nanofillers and modification additives.
The product yield and quality are improved, and the multiple stimulation response characteristics of the improved polymer polypropylene calcium salt are imparted with high mechanical strength, good biocompatibility and additional functional characteristics such as magnetic responsiveness and photocatalytic activity, which are suitable for a wider range of applications.
Smart Images

Figure CN119708299A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pharmaceutical manufacturing technology, in particular to an improved high-molecular polypropylene calcium salt and a preparation process and application thereof. Background Art
[0002] As a special polymer material, polymer polypropylene calcium is widely used in the pharmaceutical industry to treat constipation and diarrhea due to its unique chemical structure and physical properties. And because of its characteristics as a prodrug, it undergoes a decalcification reaction under the action of gastric acid to generate calcium as a by-product, so it has the unique advantage of supplementing calcium while treating. The traditional synthesis methods of polymer polypropylene calcium mainly include the following: High-pressure polymerization: First developed by Abbott Laboratories in the United States, it uses acrylic acid high-pressure polymerization, but this method requires higher temperature and pressure conditions and poses safety risks.
[0003] Azobisisobutyronitrile initiator method: It was later improved to use azobisisobutyronitrile as an initiator, which reduced the polymerization temperature and pressure requirements. However, high temperatures above 70°C may still cause acrylic acid to polymerize itself, affecting product quality and yield.
[0004] Conventional solution polymerization: usually carried out in an aqueous solution, the polymerization reaction is promoted by adding magnesium sulfate and other auxiliary reagents, but this method does not accurately control factors such as reaction time and temperature, resulting in low product yield and low calcium content in the product quality item.
[0005] Problems Although the above method has achieved the synthesis of high molecular weight polypropylene calcium to a certain extent, there are still some shortcomings: Unstable yield and quality: Traditional methods make it difficult to precisely control reaction conditions, and side reactions are prone to occur, which reduces product yield and affects the purity of the final product.
[0006] Limited functionality: Traditional polymer polypropylene calcium salt lacks special functional properties, which limits its possibility of wider application.
[0007] Poor environmental friendliness: Some traditional methods use organic solvents or other harmful chemicals, which do not conform to the principles of green chemistry and increase production costs and environmental burden. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides an improved polymer polypropylene calcium salt and a preparation process and application thereof, which solve the problems of the above-mentioned background technology.
[0009] According to a first aspect of the present invention, a process for preparing a modified polymer polypropylene calcium salt is provided, comprising the following steps: (a) preparing a magnesium sulfate solution: dissolving 500-600 parts of magnesium sulfate heptahydrate in deionized water, concentrating under reduced pressure at a temperature of 55° C.-60° C. and a vacuum degree of 0.095 MPa, and replacing the solution with nitrogen after cooling to form an oxygen-free environment to obtain the magnesium sulfate solution; (b) Preparation of a monomer mixture: under nitrogen protection, add 50-60 parts of acrylic acid, 5-10 parts of bio-based diol, 1-2 parts of functional monomer, and 100-200 parts of green initiator, and stir evenly at room temperature to prepare the monomer mixture; (c) Microwave-assisted polymerization: heating the magnesium sulfate solution to 50° C. to 55° C., adding the monomer mixture and the smart catalyst prepared in step (b) dropwise, and reacting under microwave conditions; After the addition was completed, the temperature was raised to 55°C to 60°C and polymerization aging was continued for 3 hours; Then, 200 parts of water were added and the temperature was lowered to about 30°C, and high molecular weight polypropylene was obtained by centrifugal separation; (d) cleaning and purification: the polymer polypropylene is cleaned multiple times in a continuous flow microreactor using supercritical carbon dioxide (scCO2) as a cleaning medium, each cleaning time being 10-15 minutes, until no impurities remain; (e) Intelligent calcification reaction: dispersing the cleaned high molecular weight polypropylene into a nano-scale calcium carbonate suspension, adding nano fillers, maintaining the pH value between 4.0 and 5.0, and controlling the temperature at 40° C. to 50° C. for calcification reaction for 6 hours; (f) Functional modification: During the calcification process in step (e), 1 part of a modification aid is gradually added to obtain a product; (g) drying, crushing and packaging to obtain the finished product.
[0010] According to an embodiment of the present invention, the magnesium sulfate solution concentration process in step (a) is performed by vacuum concentration and dehydration at a temperature of 55° C. to 60° C., and oxygen in the system is driven out during the concentration process, and then replaced with nitrogen to form an anaerobic condition.
[0011] According to an embodiment of the present invention, step (a) is specifically as follows: 500-600 parts of magnesium sulfate heptahydrate (MgSO4·7H2O) are dissolved in 250 parts of deionized water, and 150-200 parts of water are concentrated under reduced pressure at a temperature of 55°C to 60°C and a vacuum degree of 0.095 MPa, and then replaced with nitrogen after cooling to form an oxygen-free environment.
[0012] According to an embodiment of the present invention, the functional monomer in step (b) is selected from one or a combination of a quaternary ammonium salt group with antibacterial properties, a phenolic group with antioxidant properties, or a phosphate group capable of promoting bone growth, and the total amount does not exceed 2% of the total weight of the monomer mixture.
[0013] According to an embodiment of the present invention, in step (b), the bio-based diol is butadiene glycol.
[0014] According to an embodiment of the present invention, the green initiator is di-tert-butyl azodicarboxylate. According to an embodiment of the present invention, the smart catalyst used in step (c) is a metal organic framework; The frequency of the microwave condition is 2450 MHz, and the power is between 200 W and 400 W. The copolymerization ratio between different monomers is controlled by adjusting the microwave frequency and power.
[0015] According to an embodiment of the present invention, the nanofillers used in step (e) include but are not limited to photocatalytic materials such as TiO2 and ZnO to give the product self-cleaning, antibacterial or air purification functions, and the particle size range of the nanofillers is 10nm to 50nm.
[0016] According to an embodiment of the present invention, the modification aid used in step (f) includes but is not limited to a silane coupling agent or magnetic nanoparticles, wherein the content of the magnetic nanoparticles does not exceed 0.5% of the final product to enhance the mechanical properties, biocompatibility or impart additional functional properties of the product.
[0017] The drying comprises: after the calcification reaction is completed, the product is obtained by centrifugal separation, and is dried in a hot air circulation oven at a controlled temperature of 85°C-100°C for 3-4 hours, and after the drying loss is tested to be qualified, it is transferred to a vitrification oven and dried at a controlled temperature of 160°C-170°C for 3-4 hours.
[0018] According to an embodiment of the present invention, in step (g), the crushing and packaging comprises: the dried modified high molecular weight polypropylene calcium salt enters a conventional crusher and is crushed into white powder, and the final product is packaged in an environmentally friendly packaging material.
[0019] According to the second aspect of the present invention, there is provided a modified polymer polypropylene calcium salt having special functions or properties prepared by the above method, characterized in that the modified polymer polypropylene calcium salt has multiple stimulus response characteristics (pH sensitivity, temperature sensitivity or light sensitivity), high mechanical strength, good biocompatibility and additional functional properties (such as magnetic responsiveness or photocatalytic activity), and has a molecular weight range of 30,000 to 50,000 Daltons and a water absorption rate of 55% to 65%.
[0020] According to an embodiment of the present invention, the product is suitable for fields such as personalized treatment, intelligent medical equipment, environmental management and health care in the biomedicine industry, especially as a drug carrier, surface coating of implant materials or indoor air purification material.
[0021] Multiple stimulus response properties: By introducing different types of functional monomers, the improved polymer polypropylene calcium salt has multiple stimulus response properties such as pH sensitivity, temperature sensitivity or light sensitivity, which can be used to develop smart drug delivery systems or materials with strong environmental adaptability.
[0022] Smart catalysis and precise control: Using metal-organic frameworks (MOFs) as catalysts not only improves the selectivity and efficiency of the reaction, but also allows for more sophisticated design of the polymer structure.
[0023] Functional modification and enhancement: By adding modification agents, such as silane coupling agents or magnetic nanoparticles, the mechanical properties and biocompatibility of the modified polymer polypropylene calcium salt are enhanced, and additional functional properties, such as magnetic responsiveness, are imparted.
[0024] Photocatalytic properties: The introduction of nano-level TiO2, ZnO and other photocatalytic materials gives the modified polymer polypropylene calcium salt self-cleaning, antibacterial or air purification functions, making it suitable for more fields, such as surface coatings of medical equipment or indoor air purification materials.
[0025] Application of nano-scale calcium sources: Nano-scale calcium sources provide a larger surface area, promote the efficiency and uniformity of calcification, and improve the physical properties of the final product.
[0026] Bio-based raw materials and green solvents: The selection of raw materials from renewable resources and environmentally friendly solvents promotes sustainable development and complies with increasingly stringent environmental regulations.
[0027] This improved preparation process is not only innovative in principle, but also endows the modified polymer polypropylene calcium salt with special functions or properties through modification, making it a multifunctional, high-performance new material suitable for a wider range of applications, especially personalized treatment and smart medical devices in the biomedical industry. In addition, by introducing photocatalytic properties, the modified polymer polypropylene calcium salt can also be used in environmental governance and health care, further expanding its scope of application.
[0028] The present invention has the following beneficial effects: The present invention provides a preparation process and application of a modified high molecular weight polypropylene calcium salt having special functions or properties. The method not only improves the yield and quality of the product, but also gives the modified high molecular weight polypropylene calcium salt multiple stimulus response characteristics, high mechanical strength, good biocompatibility and additional functional characteristics.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1The present invention is a flow chart of the preparation method of the embodiment of the present invention. DETAILED DESCRIPTION
[0031] The embodiments of the present application propose an improved polymer polypropylene calcium salt and a preparation process thereof through the present invention, aiming to improve product quality and functionality by introducing functional monomers, intelligent catalysts, nanofillers and the like.
[0032] Example 1 Preparation of magnesium sulfate solution: dissolve 500 g of magnesium sulfate heptahydrate in 250 ml of deionized water, control the temperature to 55°C, and concentrate under reduced pressure to obtain 150 ml of water at a vacuum degree of 0.095 MPa. After cooling, replace with nitrogen and detect that the internal oxygen content is 0.
[0033] Preparation of monomer mixture: add 50 grams of acrylic acid, 5 grams of 96% butadiene glycol, 1 gram of quaternary ammonium salt functional monomer and 100 grams of di-tert-butyl azodicarboxylate under nitrogen protection, stir evenly at room temperature to prepare a monomer mixture for standby use.
[0034] Microwave-assisted polymerization reaction: After the magnesium sulfate solution is concentrated, it is stirred and heated to 50°C, and the monomer mixture is added dropwise. After 30 minutes of dropping, the temperature is further raised to 55°C, and the polymerization is aged for 3 hours. Then 200 ml of water is added and the temperature is lowered to about 30°C. The high molecular weight polypropylene is obtained by centrifugation.
[0035] Cleaning and purification: The polymer polypropylene was cleaned three times with scCO2 in a continuous flow microreactor for 15 minutes each time.
[0036] Intelligent calcification reaction: The cleaned high molecular weight polypropylene is dispersed into a turbid solution containing 30 grams of nano-calcium carbonate suspended in 150 milliliters of purified water, and the pH value is maintained at 4.5 and the temperature is 40°C for 6 hours.
[0037] Functional modification: 1 g of silane coupling agent was gradually added to enhance the mechanical strength.
[0038] Drying treatment: In a hot air circulation oven, control the temperature at 85℃ and dry for 3 hours, then transfer to a vitrification oven and control the temperature at 160℃ and dry for 3 hours.
[0039] Crushing and packaging: The final product is crushed and packaged in environmentally friendly packaging materials.
[0040] Test data: yield 98%, molecular weight 32,000 Daltons, water absorption rate 55%, calcium content 22%.
[0041] Example 2 Preparation of magnesium sulfate solution: dissolve 600 g of magnesium sulfate heptahydrate in 250 ml of deionized water, control the temperature to 60°C, and condense 200 ml of water under reduced pressure at a vacuum degree of 0.095 MPa. After cooling, replace with nitrogen and detect the internal oxygen content to be 0.
[0042] Preparation of monomer mixture: add 60g of acrylic acid, 10g of 96% butadiene glycol, 2g of phenolic functional monomer and 200g of di-tert-butyl azodicarboxylate under nitrogen protection, stir evenly at room temperature to prepare a monomer mixture for standby use.
[0043] Microwave-assisted polymerization reaction: After the magnesium sulfate solution is concentrated, it is stirred and heated to 55°C, and the monomer mixture is added dropwise. After 30 minutes of dropping, the temperature is further raised to 60°C, and the polymerization is aged for 3 hours. Then 200 ml of water is added and the temperature is lowered to about 30°C. Centrifugation is performed to obtain high-molecular polypropylene.
[0044] Cleaning and purification: The polymer polypropylene was cleaned three times with scCO2 in a continuous flow microreactor for 15 minutes each time.
[0045] Intelligent calcification reaction: The cleaned high molecular weight polypropylene is dispersed into a turbid solution containing 30 grams of nano-calcium carbonate suspended in 150 milliliters of purified water, and the pH value is maintained at 4.8 and the temperature is 50°C for calcification for 6 hours.
[0046] Functional modification: 1 g of magnetic nanoparticles were gradually added to impart magnetic responsiveness.
[0047] Drying treatment: In a hot air circulation oven, control the temperature at 100℃ and dry for 3 hours, then transfer to a vitrification oven and control the temperature at 170℃ and dry for 3 hours.
[0048] Crushing and packaging: The final product is crushed and packaged in environmentally friendly packaging materials.
[0049] Test data: yield 100%, molecular weight 35,000 Daltons, water absorption 60%, calcium content 22%, and magnetic response characteristics.
[0050] Example 3 Prepare magnesium sulfate solution: dissolve 550 g of magnesium sulfate heptahydrate in 250 ml of deionized water, control the temperature to 58°C, and concentrate under reduced pressure to obtain 180 ml of water at a vacuum degree of 0.095 MPa. After cooling, replace with nitrogen and detect that the internal oxygen content is 0.
[0051] Preparation of monomer mixture: add 55 g of acrylic acid, 7.5 g of 96% butadiene glycol, 1.5 g of phosphate functional monomer and 150 g of di-tert-butyl azodicarboxylate under nitrogen protection, stir evenly at room temperature to prepare a monomer mixture for standby use.
[0052] Microwave-assisted polymerization reaction: After the magnesium sulfate solution is concentrated, it is stirred and heated to 52°C, and the monomer mixture is added dropwise. After 30 minutes of dropping, the temperature is further raised to 58°C, and the polymerization is aged for 3 hours. Then 200 ml of water is added and the temperature is lowered to about 30°C. The high molecular weight polypropylene is obtained by centrifugation.
[0053] Cleaning and purification: The polymer polypropylene was cleaned three times with scCO2 in a continuous flow microreactor for 15 minutes each time.
[0054] Intelligent calcification reaction: The cleaned high molecular weight polypropylene is dispersed into a turbid solution containing 30 grams of nano-calcium carbonate suspended in 150 milliliters of purified water, and the pH value is maintained at 4.6 and the temperature is 45°C for 6 hours.
[0055] Functional modification: 0.5 g of silane coupling agent and 0.5 g of magnetic nanoparticles were gradually added to enhance the mechanical strength and impart magnetic responsiveness.
[0056] Drying treatment: In a hot air circulation oven, control the temperature at 90℃ and dry for 3 hours, then transfer to a vitrification oven and control the temperature at 165℃ and dry for 3 hours.
[0057] Crushing and packaging: The final product is crushed and packaged in environmentally friendly packaging materials.
[0058] Test data: yield 99%, molecular weight 40,000 Daltons, water absorption 65%, calcium content 22%, and has certain magnetic response characteristics.
[0059] Example 4 Preparation of magnesium sulfate solution: dissolve 525 g of magnesium sulfate heptahydrate in 250 ml of deionized water, control the temperature to 56°C, and concentrate under reduced pressure to obtain 170 ml of water at a vacuum degree of 0.095 MPa. After cooling, replace with nitrogen and detect that the internal oxygen content is 0.
[0060] Preparation of monomer mixture: add 52.5 g of acrylic acid, 7.5 g of 96% butadiene glycol, 1.5 g of TiO2 photocatalytic material and 175 g of di-tert-butyl azodicarboxylate under nitrogen protection, stir evenly at room temperature to prepare a monomer mixture for standby use.
[0061] Microwave-assisted polymerization reaction: After the magnesium sulfate solution is concentrated, it is stirred and heated to 53°C, and the monomer mixture is added dropwise. After 30 minutes of dropping, the temperature is further raised to 57°C, and the polymerization is aged for 3 hours. Then 200 ml of water is added and the temperature is lowered to about 30°C. The high molecular weight polypropylene is obtained by centrifugation.
[0062] Cleaning and purification: The polymer polypropylene was cleaned three times with scCO2 in a continuous flow microreactor for 15 minutes each time.
[0063] Intelligent calcification reaction: The cleaned high molecular weight polypropylene is dispersed into a turbid solution containing 30 grams of nano-calcium carbonate suspended in 150 milliliters of purified water, and the pH value is maintained at 4.7 and the temperature is 48°C for 6 hours.
[0064] Functional modification: 1 g of silane coupling agent was gradually added to enhance the mechanical strength.
[0065] Drying treatment: In a hot air circulation oven, control the temperature at 92℃ and dry for 3 hours, then transfer to a vitrification oven and control the temperature at 168℃ and dry for 3 hours.
[0066] Crushing and packaging: The final product is crushed and packaged in environmentally friendly packaging materials.
[0067] Test data: yield 97%, molecular weight 35,000 Daltons, water absorption 58%, calcium content 22%, good photocatalytic activity, self-cleaning and antibacterial properties.
[0068] Comparative Example 1 (Traditional High-Pressure Polymerization Method) The improved polymer polypropylene calcium salt is prepared by a traditional high-pressure polymerization method, and the specific steps are carried out according to the method of the existing document CN102516440 B.
[0069] Test data: Yield: 85% Molecular weight: 28,000 Daltons Water absorption rate: 50% Calcium content: 20% Comparative Example 2 (Conventional Solution Polymerization Method) The improved polymer polypropylene calcium salt was prepared by conventional solution polymerization method, and the specific steps were carried out according to the method of the existing document CN116675801 A.
[0070] Test data: Yield: 88% Molecular weight: 30,000 Daltons Water absorption rate: 52% Calcium content: 21% Comparative Analysis By comparing the test data of the improved polymer polypropylene calcium salt products prepared by different methods, it can be seen that the preparation process provided by the present invention has significant advantages: Improved yield: The yields of all examples are close to or reach 100%, which is much higher than the traditional method in the comparative example.
[0071] Increased molecular weight: The molecular weight of the products prepared by the method of the present invention is generally higher, reaching 32,000 to 41,000 Daltons, while the molecular weight of the products prepared by the comparative method is lower, at 28,000 and 30,000 Daltons, respectively.
[0072] Improved water absorption: The water absorption of the product prepared by the method of the present invention is higher, ranging from 57% to 62%, while the water absorption of the product prepared by the comparative method is relatively low, 50% and 52%, respectively.
[0073] Increased calcium content: The calcium content of the products prepared by the method of the present invention is also improved, ranging from 22% to 23%, while the calcium content of the products prepared by the comparative method is 20% and 21%, respectively.
[0074] Special functional properties: The products prepared by the method of the present invention also have additional functional properties, such as magnetic responsiveness and photocatalytic activity, which cannot be achieved by traditional methods.
[0075] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0076] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A process for preparing a modified polymer polypropylene calcium salt, characterized in that: The following steps are involved: (a) preparing a magnesium sulfate solution: dissolving 500-600 parts of magnesium sulfate heptahydrate in deionized water, concentrating under reduced pressure at a temperature of 55° C.-60° C. and a vacuum degree of 0.095 MPa, and replacing the solution with nitrogen after cooling to form an oxygen-free environment to obtain the magnesium sulfate solution; (b) Preparation of a monomer mixture: under nitrogen protection, add 50-60 parts of acrylic acid, 5-10 parts of bio-based diol, 1-2 parts of functional monomer, and 100-200 parts of green initiator, and stir evenly at room temperature to prepare the monomer mixture; (c) Microwave-assisted polymerization: heating the magnesium sulfate solution to 50° C. to 55° C., adding dropwise the monomer mixture and the smart catalyst prepared in step (b), and reacting under microwave conditions; After the addition was completed, the temperature was raised to 55°C to 60°C and polymerization aging was continued for 3 hours; Then, 200 parts of water were added and the temperature was lowered to about 30°C, and high molecular weight polypropylene was obtained by centrifugal separation; (d) Cleaning and purification: The polymer polypropylene is cleaned multiple times in a continuous flow microreactor using supercritical carbon dioxide as a cleaning medium, each cleaning time being 10-15 minutes, until no impurities remain; (e) Intelligent calcification reaction: dispersing the cleaned high molecular weight polypropylene into a nano-scale calcium carbonate suspension, adding nano fillers, maintaining the pH value between 4.0 and 5.0, and controlling the temperature at 40° C. to 50° C. for calcification reaction for 6 hours; (f) Functional modification: During the calcification process in step (e), 1 part of a modification aid is gradually added to obtain a product; (g) drying, crushing and packaging to obtain the finished product.
2. The preparation process according to claim 1, characterized in that: In step (g), the drying includes: after the calcification reaction is completed, the product is obtained by centrifugal separation, and the product is dried in a hot air circulation oven at a temperature of 85°C-100°C for 3-4 hours. After the drying loss is tested to be qualified, the product is transferred to a vitrification oven and dried at a temperature of 160°C-170°C for 3-4 hours.
3. The preparation process according to claim 1, characterized in that: The functional monomer in step (b) is selected from one or a combination of a quaternary ammonium salt group with antibacterial properties, a phenolic group with antioxidant properties, or a phosphate group capable of promoting bone growth; The total amount of the functional monomers does not exceed 2% of the total weight of the monomer mixture.
4. The preparation process according to claim 1, characterized in that: The smart catalyst used in step (c) is a metal organic framework; The microwave conditions have a frequency of 2450 MHz and a power between 200 W and 400 W.
5. The preparation process according to claim 1, characterized in that: The nanofiller used in step (e) comprises one or both of TiO2 and ZnO; The particle size of the nanofiller ranges from 10nm to 50nm; The nano-scale calcium carbonate suspension is a turbid solution formed by suspending 30 parts of nano-scale calcium carbonate in 150 parts of water.
6. The preparation process according to claim 1, characterized in that: In step (f), the modification aid comprises a silane coupling agent or a magnetic nanoparticle; Wherein, the content of the magnetic nanoparticles does not exceed 0.5% of the product.
7. The preparation process according to claim 1, characterized in that: In step (b), the bio-based diol is butadiene glycol; The green initiator is di-tert-butyl azodicarboxylate.
8. An improved high molecular weight polypropylene calcium salt prepared by the preparation process according to any one of claims 1 to 7.
9. The improved high molecular weight polypropylene calcium salt according to claim 8, characterized in that: The molecular weight of the improved polymer polypropylene calcium salt ranges from 30,000 to 50,000 Daltons, and the water absorption rate ranges from 55% to 65%.
10. Use of the improved high molecular weight polypropylene calcium salt according to claim 8 in drug carriers, surface coatings of implant materials or indoor air purification materials.
Citation Information
Patent Citations
Method for synthesizing calcium polycarbophil
CN102516440B
Method for synthesizing calcium polycarbophil
CN102516440A
A preparing method of a nanometer calcium carbonate / polytetrafluoroethylene composite polymer material
CN106243256A
Preparation process of calcium polycarbophil
CN116675801A